Chronic Diarrhea as a Debut Manifestation of Crohn’s Disease in Infant: Clinical Case - Anna M. Konovalova; Dmitry V. Pechkurov; Alena A. Tyazheva (Вопросы современной педиатрии)
Background. Chronic diarrhea can be a symptom of a wide variety of diseases, either of which requires special therapy approaches. The diagnosis of rare causes of chronic diarrhea is especially difficulty as it may be associated with inflammatory bowel disease (IBD) with very early (under 1 year of age) debut.Clinical case description. Boy E. had chronic diarrhea manifested on the first year of life. Ulcerative colitis was diagnosed at the age of 1.5 years, then the diagnosis was changed to Crohn’s disease at the age of 2.5 years. The results of 6-years-follow-up of the patient were presented, as well as analysis of diagnosis and treatment difficulties was carried out.Conclusion. The clinical case of Crohn’s disease with diarrhea as the leading clinical manifestation at the disease onset is described. Sequential diagnostic search allowed us to establish the diagnosis of IBD and to exclude other causes of chronic diarrhea that determined the correct therapeutic strategy.